"The Perfect Union of Man and Woman" Reclamation and Collaboration in Joseph Smith's Theology Making - Givens, Fiona (2016)
The article discusses the ideas and leadership style of Joseph Smith, Jr. an American religious leader and founder of Mormonism and the Latter Day Saint movement. It focuses on his early years leading the Church and his ideas about the Divine Feminine. It discusses his ideas and efforts to put forth the idea that a Heavenly Father and Mother co-presided in Heaven.
Keywords: History; Ideology; Mormon Church -- History; Mormons; Religious Aspects; RELIGIOUS leadership; Smith, Joseph, 1805-1844